MULTIPLES. - Murphy, Annie (Women's Review of Books)
A cartoon is presented which focuses on the impact that dissociative identity disorder (DID) has on women, including comedian, actress, author, and activist Roseanne Barr, cartoonist and computer programmer Hilda Terry, and commercial artist and art teacher Shirley Mason.